David Stevenson: Scotland's Last Royal Wedding. The Marriage of James VI and Anne of Denmark. With a Danish Account of the Marriage translated by Peter Graves. (John Donald Publishers, 1997). 158 s., 14.95 £. - E. Olesen, Jens (Historie/Jyske Samlinger, 1997)
-